MEDIA PEMBELAJARAN BIOLOGI BERBASIS ADOBE ANIMATED MENGGUNAKAN MODEL RADEC (READ, ANSWER, DISCUSS, EXPLAIN, CREATE) MATERI SISTEM RESPIRASI KELAS XI - Lutfi Azis; Triana Asih (BIOEDUKASI (Jurnal Pendidikan Biologi), 2022)
The 21st century is a shift to the digital era in which information is growing too fast and human activities can be visualized by smartphones, it demands education to follow the digital era to minimize the lack of the utilization of smartphones as a learning media in learning model and material. The objective of this study is to produce Biology’s learning media products based on Adobe Animated using the RADEC learning model in the respiratory system material which is decent in the learning process. This study used the 4D research development model. This study only used 3 stages of 4 stages, namely Define, Design, Develop and Disseminate. The data analysis technique of this study is a questionnaire that was distributed to the students in a small group trial, before the trials the media was validated by experts. The learning media was produced after validation and revision, the average percentage from design experts scored is 92%, the material expert got 90% percentage and small group trials are 92%. Based on the percentage from the design experts, material experts, and a small group trial, the learning media was included in the "Very Appropriate" category. Therefore, it can be used by the students and teachers in the learning process. Kata Kunci : RADEC, Adobe Animated, Media Pembelajaran, Biologi, Sistem Respirasi